Superior Vena Cava Syndrome: Etiologies, Manifestations, and Treatments - Quencer, Keith B. (Seminars in Interventional Radiology, 2022)
Superior vena cava (SVC) obstruction, whether from benign or malignant causes, results in a variety of symptoms. It is a potential medical emergency when cerebral or laryngeal edema occurs. Endovascular therapy is the treatment of choice for patients in need of emergent relief of symptoms. This article will provide a review of SVC syndrome with a focus on endovascular treatment techniques.
Keywords: SVC syndrome; SVC stenting; stent migration; pericardial tamponade; interventional radiology